Register of Oncological Diseases in Canton Sarajevo - Masic, Izet (AVICENA, d.o.o., Sarajevo, 2009)
CONFLICT OF INTEREST: NONE DECLARED SUMMARY: The register of oncological diseases in Canton Sarajevo is important as it can be used to track and improve healthcare, especially in older age groups. The oncological registers are a way of recording data, suitable as a source of indicators. In the analyzed register, 1124 new cases of malignancy were recorded. There are slightly more malignant diseases in male (53%). The incidence of cancer varies depending of the age of patients. This analysis gives us important estimation in the relation of cancer morbidity, cancer types, age distribution, demographic factors, cancer stages and important cancer risks. The register and the analysis give us a chance for correlating and comparing the state of oncological diseases with other countries.